If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 22 = 6y + -5 + -3 Reorder the terms: 22 = -5 + -3 + 6y Combine like terms: -5 + -3 = -8 22 = -8 + 6y Solving 22 = -8 + 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. 22 + -6y = -8 + 6y + -6y Combine like terms: 6y + -6y = 0 22 + -6y = -8 + 0 22 + -6y = -8 Add '-22' to each side of the equation. 22 + -22 + -6y = -8 + -22 Combine like terms: 22 + -22 = 0 0 + -6y = -8 + -22 -6y = -8 + -22 Combine like terms: -8 + -22 = -30 -6y = -30 Divide each side by '-6'. y = 5 Simplifying y = 5
| -42+39= | | x-4=-5x-2 | | 1/2(6x-4)=8-3x | | 8-3(p-4)=wp | | -b-3b-9-(-4)=-17 | | -6x+2=-41 | | -2y+7=-9 | | 9(f+-6)=-15 | | 2+4v=8 | | f(x)=(3x^2+2x+1)6 | | 12x+-2y=-12x+755 | | 9.2t=6.3t-7.25 | | 60(17.5)+150y=1200 | | 12x+-2y=-12x+9 | | (x-32)/1.8=-35 | | (-16x^4)-(32x^3)-(80x^2)=0 | | 10+3k=22 | | 44=-5s+84 | | 60(7.5)+150y=1200 | | 2/3a-3/4=3/4 | | 33/4x5-4 | | 2+4v=18 | | -8y+23=3(y-7) | | 14-w/8=4x-9 | | 5n-7(n+3)=-25-2n | | -27a^4b^3/3ab | | 12+-2y=-12+-13 | | 1+s=3 | | -d/-12-6=1 | | 25=12a+61 | | 2(a+12)=50 | | 12+-2y=12+-13 |